Smart Test Execution of Android Compatibility Tests - Castro, Alice; Barbosa, Heryck; Albuquerque, Abda; Porty, Roger (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2024: Anais do IX Simpósio Brasileiro de Testes de Software Sistemático e AutomatizadoDO - 10.5753/sast.2024.3722, 2024)
With technology and internet expansion, the demand for software services has increased. As a result, these services have shifted from individual machines to being hosted on servers for remote access. This paper presents Smartgate, a web service that processes tasks from our request manager, accepting or rejecting them and starting Normal Exception (NE) scope tests. It provides early results to reduce the execution time of tests carried out by engineers and avoids human errors in the process, whether during system development or on the part of the test engineer. The data available in the task needs to be reviewed and validated for Smartgate to start correctly. Now, Smartgate has gained space in our software testing process after serving 53.16% of Normal Exception requests created and submitted from 2021 to 2023.